(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Horbatiuk R., Turanov Y. The using of the modern information technologies in the training of teachers of the technologies. The article indicated the importance of training in the preparation of future teachers of technology of modern information technology. Established that the application of computer tools makes the learning process smarter and more effective. Focused attention on the implementation of the educational process elements of computer aided design.